KARAKTERISTIK FUNGSI KELENJAR TIROID PASCA TIROIDEKTOMI TOTAL PADA PASIEN NODUL TIROID DI RSUP SANGLAH - Pamungkas, Kadek Mercu Narapati (E-Jurnal Medika Udayana, 2022)
ABSTRACT The thyroid nodule is an enlargement because of the impact of TSH stimulation in order to produce thyroxine. The thyroid nodule is a case of benign and malignant neoplasm with a prevalence rate of 5-10%. The thyroid nodule causes obstruction and cosmetic disturbance so that these need thyroid gland surgery or thyroidectomy. Thyroidectomy is categorized into two methods which are partial and total thyroidectomy. After thyroidectomy procedure is performed, it needs subsequent examination post thyroidectomy in order to check the thyroid gland functions (hypothyroid, euthyroid and hyperthyroid). Such examination consists of the examination of TSH and FT4 levels. This study aims to understand the characteristics in terms of age, sex, classification and thyroid gland post total thyroidectomy. This study is of a descriptive research type with cross-sectional design towards thyroid nodule patients in RSUP Sanglah from November 2018 until November 2019. This study uses secondary data in the form of thyroid nodule patients’ medical records to get the characteristics in terms of age, sex, classification and thyroid gland post total thyroidectomy. In this study, it was found that 59 patients’ medical records with highest category which is with the age 50-59 years (30.5%); thyroid nodule cases are suffered more by female patients (84.7%) and was found more to be malignant (59.3%) which the domination of papillary thryroid carcinoma (45.8%). The thyroid gland function characteristics which are with the most cases are hypothyroid (44.1%), as followed by hyperthyroid (37.3%) and euthyroid (18.6%). It can be concluded that the thyroid nodule cases happen most in 50-59 years old with case with more prevalence in female patients. The thyroid nodule is found more to be in malignant classification. The thyroid gland function post thyroidectomy being found to be with most prevelence is hyperthyroid. Keywords : Thyroid nodule, thyroidectomy, thyroid function